Impact of small prosthesis size on transcatheter or surgical aortic valve replacement outcomes. Issue 4 (4th May 2017) - Salna, Michael; Khalique, Omar K.; Chiuzan, Codruta; Kurlansky, Paul; Borger, Michael A.; Hahn, Rebecca T.; Leon, Martin B.; Smith, Craig R.; Kodali, Susheel K.; George, Isaac
Abstract : Objectives: Determine the comparative impact of small prosthesis size on transcatheter and surgical aortic valve replacement (SAVR) outcomes. Background: Patients with small aortic annuli tend to have worse postoperative outcomes and hemodynamics. We sought to describe surgical outcomes in patients with very small aortic annuli and then compare early hemodynamic and clinical outcomes in patients undergoing surgical or transcatheter aortic valve replacement (TAVR) with the smallest available valves to assist in optimal prosthesis selection for this challenging patient population. Methods: A retrospective single‐center study comparing patient data from 2143 patients undergoing SAVR with valves having a true internal diameter (ID) of ≥19 mm with 130 patients receiving surgical valves with true ID's <19 mm (SmSAVR). Outcomes of SmSAVR patients were then compared with 40 patients undergoing TAVR receiving small valves (SmTAVR). A representative SmSAVR cohort was then compared with the SmTAVR patients for post‐operative hemodynamics. Results: Receiving a small surgical valve may significantly increase 1‐year mortality compared with standard‐sized surgical valves (HR 1.93; 95% confidence interval 1.03–3.61). SmTAVR patients had significantly shorter lengths of stay than SmSAVR (median 5 vs. 9 days), and significantly better postoperative hemodynamic profiles (mean gradient 13.4 ± 7.8 vs. 18.1 ± 8.4 mm Hg, P = 0.006, peak velocity of 2.5 ± 0.6 vs. 2.9 ± 0.6 m/s, P = 0.003). Conclusions: TAVR is a safe and reasonable option for patients with small aortic annuli and is associated with shorter hospital stays and more favorable postoperative hemodynamic outcomes compared with SAVR. © 2017 Wiley Periodicals, Inc.